Stem Cell Transplantation in Scleroderma Therapy - Ali, Buthaina Ahmed (faculty of Basic Medical Science - Libyan International Medical University, 2018)
The new studies on Scleroderma therebyare Support for using hematopoietic stem cell therapy (HSCT) for SSc , which shows that stem cell transplants can provide better long-term benefits than the standard treatment for patients with severe scleroderma.
stem cell transplant A procedure in which a patient receives healthy bloodforming cells (stem cells) to replace their own that have been destroyed by disease or by the radiation or high doses of anticancer drugs that are given as part of the procedure. The healthy stem cells may come from the blood or bone marrow of the patient, from a donor, or from the umbilical cord blood of a newborn baby. A stem cell transplant may be autologous (using a patient’s own stem cells that were collected and saved before treatment), allogeneic (using stem cells donated by someone who is not an identical twin), or syngeneic (using stem cells donated by an identical twin